The shadow of the Balbina dam: A synthesis of over 35 years of downstream impacts on floodplain forests in Central Amazonia - Schöngart, Jochen; Wittmann, Florian Karl; Faria de Resende, Angélica; Assahira, Cyro; de Sousa Lobo, Guilherme; Rocha Duarte Neves, Juliana; da Rocha, Maíra; Biem Mori, Gisele; Costa Quaresma, Adriano; Oreste Demarchi, Layon; Weiss Albuquerque, Bianca; Oliveira Feitosa, Yuri; et al. (Aquatic Conservation: Marine and Freshwater Ecosystems, 2021)
The Balbina hydropower dam in the Central Amazon basin, established in the Uatumã River in the 1980s, is emblematic for its socio-environmental disaster. Its environmental impacts go far beyond the reservoir and dam, however, affecting the floodplain forests (igapó) in the downstream area (dam shadow), which have been assessed using a transdisciplinary research approach, synthesized in this review. Floodplain tree species are adapted to a regular and predictable flood pulse, with high- and low-water periods occurring during the year. This was severely affected by the operation of the Balbina dam, which caused the suppression of both the aquatic phase at higher floodplain elevations and the terrestrial phase at lower floodplain elevations (termed the ‘sandwich effect’). During the period of construction and reservoir fill, large-scale mortality already occurred in the floodplains of the dam shadow as a result of reduced stream flow, in synergy with severe drought conditions induced by El Niño events, causing hydraulic failure and making floodplains vulnerable to wildfires. During the operational period of the dam, permanent flooding conditions at low topographical elevations resulted in massive tree mortality. So far, 12% of the igapó forests have died along a downstream river stretch of more than 125 km. As a result of flood suppression at the highest elevations, an encroachment of secondary tree species from upland (terra firme) forests occurred. More than 35 years after the implementation of the Balbina dam, the downstream impacts caused massive losses of macrohabitats, ecosystem services, and diversity of flood-adapted tree species, probably cascading down to the entire food web, which must be considered in conservation management. These findings are discussed critically, emphasizing the urgent need for the Brazilian environmental regulatory agencies to incorporate downstream impacts in the environmental assessments of several dam projects planned for the Amazon region. © 2021 John Wiley & Sons, Ltd.
Keywords: disturbance; flood pulse; hydropower dam; igapó; long-term ecological research (LTER); tree mortality; Uatumã River; wildfire